Biometry and gas exchange in clonal cuttings coffee submitted to different substrates - Alves, Erilene Romeiro; Schmidt, Raquel; Moreira, Riziely; Dias, Jairo Rafael Machado; Maia, Emanuel (Coffee Science - ISSN 1984-3909, 2017)
Aimed to evaluate the biometry and leaf gas exchange of Coffea canephora seedlings submitted to different substrates, in five evaluation periods. The experiment was carried out in Rolim de Moura, Rondônia. It was conducted in a split plot scheme in time, composed by the combination of three substrates (soil, organic compost and commercial substrate) with five assessment periods (25, 50, 75, 100, 125) days after planting the cuttings and parallel 75 , 100 and 125 DAE between 9 and 11 hours, we evaluated the leaf gas exchange. The organic substrate is a favorable alternative, presenting higher in biometric characteristics compared to the soil and commercial substrate in the formation of clonal coffee canephorus seedlings during the formation stage in the nursery. Different substrates used in this study were not able to make changes in gas exchange in the clonal seedlings of trees.